2023
DOI: 10.11604/pamj.2023.45.110.37095
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy in African children infected with HIV/AIDS: a case control study

Abstract: Introduction left ventricular hypertrophy (LVH) measured by echocardiography seen in human immunodeficiency virus/acquired immunodeficiency disease (HIV/AIDS) affects the morbidity and mortality. The hemodynamic and metabolic changes in (HIV/AIDS) affect the heart adversely causing hypertrophic remodeling with left ventricular hypertrophy. The aim of this study was to determine the prevalence and risk factors associated with LVH in African children with HIV/AIDS. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In another study, LVH was found in 6.5% of transesophageal echocardiographic examinations among PLWH [18]. LVH and increased RWT are common among children with HIV/AIDS (LVH present in 66.7% cases) [19]. All these studies reported an association between low CD4 + cell count and LVH.…”
Section: Discussionmentioning
confidence: 93%
“…In another study, LVH was found in 6.5% of transesophageal echocardiographic examinations among PLWH [18]. LVH and increased RWT are common among children with HIV/AIDS (LVH present in 66.7% cases) [19]. All these studies reported an association between low CD4 + cell count and LVH.…”
Section: Discussionmentioning
confidence: 93%